2017
DOI: 10.3390/ijerph14020159
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Knowledge Level, Attitudes, Risky Behaviors and Preventive Practices on Sexually Transmitted Diseases among University Students as Future Healthcare Providers in the Central Zone of Malaysia: A Cross-Sectional Study

Abstract: This study was done to assess the knowledge, attitudes, risky behaviors and preventive practices related to sexually-transmitted diseases (STDs) among health and non-health sciences university students as future healthcare providers in Malaysia. A total of 700 health and non-health sciences university students (255 male; 445 female) aged between 17 and 30 years were surveyed by using a self-administered questionnaire. The majority (86.6%) had heard of STDs, and 50.4% knew STDs could present without symptoms. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
83
7
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(129 citation statements)
references
References 28 publications
25
83
7
14
Order By: Relevance
“…Therefore, this study was designed to investigate the knowledge of STDs among young adults living in the Albaha region in Saudi Arabia and registered as undergraduate students in Albaha University. Findings reported in this study were consistent with evidence from previous literature [13][14][15][16]. Thus, the current work supports the suggestion that…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, this study was designed to investigate the knowledge of STDs among young adults living in the Albaha region in Saudi Arabia and registered as undergraduate students in Albaha University. Findings reported in this study were consistent with evidence from previous literature [13][14][15][16]. Thus, the current work supports the suggestion that…”
Section: Discussionsupporting
confidence: 93%
“…Female participants showed higher STDs-KS compared to male students, which is consistent with few previous studies [4,13]. The question remains: is the risk of accruing and transmitting STDs among Saudis male and female is equal?…”
Section: Discussionsupporting
confidence: 90%
“…The sexual behaviour of young people therefore constitutes a major risk factor in contracting HIV/AIDS and other sexually transmitted diseases. Inconsistent use of condoms, a high number of different sexual partners, having sex after drinking alcohol and the low frequency of HIV testing are the most frequent risk behaviours reported in international research (Castro & Santos-Iglesias, 2016;Cortés Alfaro, García Roche, & Ochoa Soto, 2015;Fernández-Silva & Sánchez-Martínez, 2018;Folasayo et al, 2017;Xu et al, 2019;Mavhandu-Mudzusi & Asgedom, 2016;Othieno, Okoth, Peltzer, Pengpid & Malla, 2015;Thomas, Yarandi, Dalmida, Frados & Klienert, 2015). Previous studies showed that Spanish young people do not use condoms consistently (Bagmato, Jenaro, Flores & Guzmán, 2014;Ballester, Gil, Jiménez & Ruiz, 2009;Castro & Santos-Iglesias, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…14 Although data indicate that the prevalence of non-knowledge decreases as the years of study increase, a more recent article showed that, even among university students, 14% did not know about STIs, 50.4% knew that they could be asymptomatic, 63.8% knew about the use of condoms, but that 66.7% of the sexually active had multiple partners. 18 The sample of this study also reveals that the gender, especially the unprotected, is independent of the level of schooling, although it is expected that individuals with university level, with greater access to information, will be more aware of the care with their protection and, consequently, , the lower the risk of contracting STIs. 14 The facilities of modern life and the increase in life expectancy, which in this case include hormonal replacement and medications to improve sexual performance, have allowed the elderly the opportunity to rediscover new experiences, among them, the experience of sexuality.…”
mentioning
confidence: 98%
“…These behaviors are more frequent in homosexuals and bisexuals, however, the data show that heterosexuals, over the years, have tended to present the same behavior, as already pointed out by Folasayo et al, 2017. 18 Considering that heterosexuals, homosexuals and bisexuals have shown partner variability and that this percentage has been increasing in recent years, reducing almost half those with a single partner, associated with the non-use of condoms, increases the vulnerability in contracting STI to all groups, since even consistent use of condoms is not enough to prevent the transmission of some agents such as HPV, genital herpes and others. 12 The use of condoms was another interesting point, since, according to the users' discourse, most had a significant practice, although almost half had previously had an STI and was attending the service by some of them.…”
mentioning
confidence: 99%